ФАКТОРЫ ЭФФЕКТИВНОГО ВОСПРИЯТИЯ ОБРАЗОВАТЕЛьНЫХ ТЕЛЕ- И РАДИОПЕРЕДАЧ (Journal of Oriental Studies, 2018)
This article is devoted to the study of the influence of educational television and radio programson the worldview of the Japanese. The purpose of this work is to reveal the features of Japan’s educationaltelevision and radio programs that contribute to the personal development of society. The articleused the method of content analysis of TV and radio broadcasts and a questionnaire study. Students ofbachelor’s and master’s degrees of universities were selected as respondents. Due to close cooperationbetween KazNU al-Farabi and Japanese universities, the survey was facilitated by teachers and professorsfrom well-known universities in Japan: Waseda University, Tokyo University of Foreign Languagesand Tsukuba University. The survey was conducted electronically anonymously, and in the format of anInternet survey.The use of educational television and radio programs in practice, namely in the sphere of studyingJapanese language and literature, presumably can increase the level of students’ education, and providenew interactive methods of teaching and learning that will bring the interaction of the media and theeducational system to a new level.